1986
DOI: 10.1029/ja091ia01p00101
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of nonoscillatory mirror waves at the Earth's magnetosheath

Abstract: The generation of nonoscillatory mirror waves is studied using a one‐dimensional periodic hybrid electromagnetic simulation. The ion dynamics are treated exactly; the electrons are approximated as a finite pressure, massless fluid. Compression of the flux tubes in the magnetosheath causes a large pressure anisotropy, and it has been proposed that this anisotropy drives a mirror instability. The mirror waves have been identified by large amplitude fluctuations of the magnetic field, anticorrelated with pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
142
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 47 publications
9
142
0
Order By: Relevance
“…A study by Price et al (1986) showed that the angle between maximum variance direction and background field was smaller than 30…”
Section: Crossing From 6 To 7 June: Mirror-mode Wavesmentioning
confidence: 99%
“…A study by Price et al (1986) showed that the angle between maximum variance direction and background field was smaller than 30…”
Section: Crossing From 6 To 7 June: Mirror-mode Wavesmentioning
confidence: 99%
“…The second instability to operate under conditions of temperature anisotropy is the mirror instability. The growth rates of EMIC waves would be expected to dominate those of mirror structures in a purely proton plasma, but the presence of additional cold ion species, such as helium, is thought to suppress the ion cyclotron instability (Price et al, 1986;Gary et al, 1993). Empirically, therefore, the mirror instability dominates under conditions of moderate temperature anisotropy and high beta, and generates strongly compressive (frequently showing DB/B $ 1), linearly polarised, non-propagating structures.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that mirrormode waves have been observed in such environments with and without the presence of ion-cyclotron waves is still an issue of study. It has been suggested, for instance, that the addition of a helium component can suppress the growth rate for ion-cyclotron waves [Price et al, 1986;Gary, 1993] and favor the growth of mirror modes. Likewise, inhomogeneites created in the background plasma by mirror modes can inhibit the growth of ion-cyclotron waves [Southwood and Kivelson, 1993].…”
Section: Introductionmentioning
confidence: 99%